Divergence studies in early-maturing soybean (Glycine max (L.) Merrill) germplasm acceáions in India - Bharadwaj, Ch.=700 1 Tara Satyavathi, C.
(En, Fr, Es)
ilus., 10 ref.
Keywords: GLYCINE MAX; GERMOPLASMA; MADURACION; ITALIA; PLASMA GERMINAL